Geocryological conditions of the Urals-Pai-Khoi mountain system - V S.M. Fotie (Известия высших учебных заведений: Геология и разведка)
Contemporary geocryological conditions of the Urals-Pai-Khoi mountain system has been considered as a result of the repeated and significant changes of the severity of the climatic and geocryological conditions. It has been demonstrated that during all the cryogenic period as well as at nowadays, the formation of the rock temperature, the thickness, the discontinuosity and the structure of the cryogenic strata obeyed and obey the laws of latitude and altitude zoning. The given characteristics of the contemporary cryogenic strata for the segments of Urals and Pai-Khoi illustrate clearly the significant changes in rock temperature (from +3 to -11°C), in thickness (from 0 to 1000 m), discontinuities and structure of the cryogenic strata at the increase both in latitude and in altitude of the area.